2021
DOI: 10.1055/s-0041-1727299
|View full text |Cite
|
Sign up to set email alerts
|

Rare Clinical Presentation in a Case of Pediatric Guillain-Barré Syndrome and Rehabilitation Outcome

Abstract: Nearly half of patients with Guillain-Barré syndrome (GBS) have cranial nerve involvement. Ocular muscle weakness or ophthalmoplegia occurs in ~10% of these patients. Patients presenting with bilateral ptosis, with or without ophthalmoplegia, is a rare finding. Anti-GQ1b antibody has been found in Miller Fisher syndrome and GBS with ophthalmoplegia variants. We report a case of GBS in a young boy presenting with rare presentation of tetraplegia, bilateral ptosis, and facial palsy, no ataxia but ophthalmoplegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…By the time of discharge, patient scored 20 on AM-PAC indicating 36% impairment, which was 41% improvement from admission. Sharma et al [35] reported a case report of 7 year old boy with normal birth and development associated with no prior illness presented with tetroplgia, facial palsy and opthamoplegia with posies and sernegative anti-GQ1b antibody was started on intravenous immunoglobulin showed inadequate response and referred for inpatient rehabilitation. Rehabilitation was focused with goal to prevent complication and maximize Functional ability.…”
Section: Many Previous Studies Have Reported Gbs Disease In Childrenmentioning
confidence: 99%
“…By the time of discharge, patient scored 20 on AM-PAC indicating 36% impairment, which was 41% improvement from admission. Sharma et al [35] reported a case report of 7 year old boy with normal birth and development associated with no prior illness presented with tetroplgia, facial palsy and opthamoplegia with posies and sernegative anti-GQ1b antibody was started on intravenous immunoglobulin showed inadequate response and referred for inpatient rehabilitation. Rehabilitation was focused with goal to prevent complication and maximize Functional ability.…”
Section: Many Previous Studies Have Reported Gbs Disease In Childrenmentioning
confidence: 99%